Perancangan Antena Luar Ruangan (Outdoor) Mikrostrip Mimo Rectangular Patch 28 Ghz Untuk Jaringan Komunikasi Nirkabel 5G - Mustofa, Ivan Rafli; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Nowadays, intensive research on 5G MIMO microstrip antenna is increasing due to the high data rate required. Frequency 28 GHz is one of the allocation frequency approved by FCC. In this paper, MIMO 2x2 microstrip patch antenna using microstrip feeding line is dessigned for 5G wireless communication network. This antenna uses an array technique to increase the gain of the antenna. The antenna is designed and simulated using CST Microwave Studio simulation software and operated at 28 GHz. From the simulation result, the impedance bandwidth obtained is 1,95 GHz or 6,96% with return loss of -44,77dB, the simulated gain reaches 18,5 dBi. The designed MIMO 2x2 microstrip antenna meets the 5G requirements.Keywords : 5G Antenna, MIMO, Dual-Band Antenna, Microstrip Antenna Array.